Sarana dan Prasarana Rumah Sakit Pemerintah dalam Upaya Pencegahan dan Pengendalian Infeksi di Indonesia - Herman, Max Joseph; Handayani, Rini Sasanti (Jurnal Kefarmasian Indonesia, 2016)
Nosocomial infections is an important issue around the world. Hospitals are required to provide qualified, efficient and effective service to ensure patient safety. The Ministry of Health has revitalized prevention and control of infection program (PPI) in hospitals which is one of the cornerstones towards patient Safety. The purpose of this study is to identify the preparedness of hospitals to implement the PPI program. The data source is Health Facility Research of 2011 which was done by National Institute of Health Research and Development. The aspects examined include facility, infrastructure, human resource, organization, guidelines, compliance in prescribing, the availability of clean water and hospital sewage treatment. The results show that many hospitals are not yet ready to conduct PPI, especially in terms of infrastructure, clean water sterilization and processing waste, mostly hospitals of classes C and D. Sewage treatment is important in the control or prevention of spread of antimicrobial resistance. This program gives many benefits especially in preventing the occurrence of total resistance or back to the era before antibiotics. The PPI program does require a large fee such that hospital management often disapproves, although the result of available cost analysis indicates that PPI is highly cost-effective.